Non-Coding RNAs in Retinoblastoma - Plousiou, Meropi; Vannini, Ivan (Frontiers in Genetics, 2019)
Retinoblastoma (Rb) is the most common ocular pediatric malignancy that arises from the retina and is caused by a mutation of the two alleles of the tumor suppressor gene, RB1. Although early detection provides the opportunity of controlling the primary tumor with effective therapies, metastatic activity is fatal. Non-coding RNAs (ncRNAs) have emerged as important modifiers of a plethora of biological mechanisms including those involved in cancer. They are classified into short and long ncRNAs according to their length. Deregulation of all these molecules has also been shown to play a critical role in Rb pathogenesis and progression. It is believed that ncRNAs can provide new insights into novel regulatory mechanisms associated with clinical pathological characteristics, facilitating the development of therapeutic alternatives for the treatment of Rb. In this review we describe a variety of ncRNAs which, capable of regulating the most likely candidate genes involved in the tumorigenesis of Rb, could prove useful in analyzing different aspects of this cancer.